Low-carbon development policies and achievements in the context of the livestock sector in China - Sha WEI; Junming FAN; Yanfeng TIAN; Hongmin DONG (Frontiers of Agricultural Science and Engineering)
● The main impediments to low-carbon development of livestock sector are recognized. ● The divergence between the existing policies and actual practices are explained. ● Policy should focus on establishing standards, database and monitoring network. Rapid growth and a vast transition of Chinese livestock industry driven by economic incentives make it become an important contributor on climate change over the last four decades. This study first analyzes the evolving low-carbon livestock development policies and regulations, then an assessment and explanations of the achievements and non-achievements are provided. The findings reveal that China began to pay attention to low-carbon development policy starting in the early 1990s. However, only after the cyclic and green concept became the main sustainable development policy, China began to move seriously toward low-carbon livestock development. Several policy instruments were introduced, including moderate scale, feed optimization, manure resource utilization, facility and equipment allocation rate, energy conservation and substitution. Overall, achievements were made in introducing such policies. However, due to the large share of standard agriculture and regional resources, and environmental diversity, such policies may have little effect in practice. The divergence between the policies and actual practices are explained, and important policies applicable to all developing countries are also recommended.